PENGGUNAAN TINDAKAN TEMBAK DI TEMPAT TERHADAP PELAKU TERORISME OLEH DENSUS 88 DIKAITKAN DENGAN ASAS PRADUGA TIDAK BERSALAH - salem, agus (UNES Law Review, 2018)
In recent years terrorism has become increasingly prevalent and shootings have often been carried out against terrorists against the police. In action against the perpetrators of theorism, Densus 88 often took action to place a shot. Such actions cause opposition to the principle of presumption of innocence. The specifications in this study are descriptive analytical. The results of the study are the rule of law which is the basis of the shooting in place against terrorists is Article 50 and 51 of the Criminal Code. The Chief of Police Regulation No. 1 of 2009 concerning the use of force in the Police Action is a number of basic principles on which firearms are used. Detachment 88 as the perpetrator of terrorism crackdown operations must pay attention to the principle of presumption of innocence by avoiding arbitrary actions and being outside the established procedures, both in law and other regulations.